A HYPOTHESIS OF RADIORESISTANCE AND CELL-SURVIVAL CURVE SHAPE BASED ON CELL-CYCLE PROGRESSION AND DAMAGE TOLERANCE. Issue 1 (11th December 2018) - Herskind, Carsten; Liu, Qi; Liu, Xiaolei; Zhang, Yingying; Ma, Lin; Angelie, Elsa; Ma, Hui Hui; Liu, Junqi; Giordano, Frank A; Wenz, Frederik; Veldwijk, Marlon R
Abstract: Exponential survival curves of early-passage human fibroblasts challenge classic biophysical models of cell inactivation. Thus, X-ray doses of 2–4 Gy inactivate normal, human skin fibroblasts in spite of negligible residual double-strand breaks. By contrast, radioresistant p53-mutant U251 glioblastoma cells proliferate in spite of residual damage. Similarly, p53 wildtype TK6 lymphoblastoid cells show exponential survival curves while the related p53-mutant WTK1 cell line continued to proliferate and showed a shouldered survival curve. Here, we propose a model in which the radioresistant shoulder region is due to tolerance to certain types or amounts of residual damage that would otherwise inactivate normal cells. Thus, the steeper initial slope and absence of a shoulder in the survival curve of normal cells may not imply a higher number of residual lesions but rather non-tolerance to these lesions.